2015
DOI: 10.2147/ijn.s73916
|View full text |Cite
|
Sign up to set email alerts
|

Competitive inhibition of survivin using a cell-permeable recombinant protein induces cancer-specific apoptosis in colon cancer model

Abstract: Endogenous survivin expression has been related with cancer survival, drug resistance, and metastasis. Therapies targeting survivin have been shown to significantly inhibit tumor growth and recurrence. We found out that a cell-permeable dominant negative survivin (SurR9-C84A, referred to as SR9) competitively inhibited endogenous survivin and blocked the cell cycle at the G 1 /S phase. Nanoencapsulation in mucoadhesive chitosan nanoparticles (CHNP) substantially increased the bioavailabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This could be mainly due to the overexpression of endogenous survivin in the TGF-β induced myofibroblasts. Previous study has shown that SurR9-C84A induces apoptosis in cancer cells which over-express survivin, by intrinsic apoptosis pathway in G 1 /S phase of cell cycle (Roy et al, 2015a ). However, here we found that, the combination of TSA and SurR9-C84A was more effective than SurR9-C84A alone in inducing cell death in myofibroblast cells, showing a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be mainly due to the overexpression of endogenous survivin in the TGF-β induced myofibroblasts. Previous study has shown that SurR9-C84A induces apoptosis in cancer cells which over-express survivin, by intrinsic apoptosis pathway in G 1 /S phase of cell cycle (Roy et al, 2015a ). However, here we found that, the combination of TSA and SurR9-C84A was more effective than SurR9-C84A alone in inducing cell death in myofibroblast cells, showing a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we synthesized a dominant negative protein (SurR9-C84A) which targets the wild type survivin. Previous studies have revealed that SurR9-C84A replaces the depleted endogenous survivin in normal brain cells and helps in their proliferation (Baratchi et al, 2010 ; Sriramoju et al, 2014 ), while in the case of cancer cells, SurR9-C84A binds to the highly overexpressed survivin to form a heterodimer and leading to its degradation by ubiquitination and apoptosis (Cheung et al, 2010 ; Roy et al, 2015a ).…”
Section: Introductionmentioning
confidence: 99%
“…Co-delivery NF-ĸB inhibitor, IMD-0354 and chemotherapeutic agent Doxorubicin, encapsulated in ligand targeted nanoparticle, effectively targeted tumor microenvironment by increasing sensitivity and reducing cytotoxicity of Doxorubicin [263]. Chitosan nanoparticle encapsulated dominant negative survivin, competitively inhibited the endogenous protein, specifically in survivin overexpressing CSCs [264]. They have been used in delivery of survivin inhibitors, alone or in combination with chemotherapeutic agents for synergistic downregulation of survivin.…”
Section: Targeted Drug Delivery Using Nanocomplexesmentioning
confidence: 99%
“…Thus, due to their specific physical properties, once they get into the tumoral tissue, nanobioconjugate could facilitate early diagnosis, even in the early stage of molecular damage (Karmakar et al 2012;Rees and Moghimi 2012;Soster et al 2012;Laroui et al 2013;Roy et al 2015). In terms of cancer therapy, using nanoparticles (NPs), through its potential of targeted and localized delivery of chemotherapeutic drugs with selective destruction of cancerous cells, can lead to overcoming the problems of resistance to chemotherapeutic agents and their adverse effects (Bertrand et al 2013;Nichols and Bae 2013;Yeo 2013;Sun et al 2014;Ediriwickrema and Saltzman 2015).…”
Section: Introductionmentioning
confidence: 99%